Development of bacterial wilt resistant F1 hybrid(s) in chilli (Capsicum annuum L.) - Nimisha Sara James (Department of Olericulture,College of Horticulture, 2016)
A study on the ‘Development of bacterial wilt resistant F₁ hybrid(s) in chilli (Capsicum annuum L.)’ was conducted at the Department of Olericulture, College of Horticulture, Vellanikkara during May 2015 to March 2016. The investigation was done in three experiments with the objective to develop high yielding bacterial wilt resistant F1 hybrids in chilli and to estimate combining ability and heterosis for yield and yield components. The bacterial wilt resistant parents viz. Ujwala, Anugraha, VKC 2, VKC 11 and VKC 76 were crossed in a diallel pattern without reciprocals to produce ten F1 hybrids. These hybrids along with their parents were evaluated in the field in a randomized block design to estimate mean performance, combining ability, heterosis and bacterial wilt resistance. The hybrids performed better than parents in the case of plant height, fruit length, fruit width and fruit girth in the cross VKC 11 x VKC 76, average fruit weight in VKC 2 x VKC 76, capsaicin content in Anugraha x VKC 2 and beta carotene in VKC 2 x VKC 11. The good general combiner for the number of fruits per plant and yield was Anugraha. Ujwala and Anugraha were found to be good general combiners for the content of phosphorus, calcium, magnesium and beta carotene. VKC 11 showed high general combining ability in fruit length, fruit girth, magnesium, iron, vitamin C and beta carotene. The study carried out on the general and specific combining ability revealed that there was preponderance of non additive gene action for plant height, number of branches, days to flower, days to harvest, days from flowering to harvest, fruit width, fruit girth, average fruit weight, yield per plant , phosphorus, calcium, magnesium, iron and antioxidant activity. Number of fruits per plant, capsaicin, vitamin C and beta carotene were governed by additive gene action. Highest sca effects were observed for plant height in Anugraha x VKC 76, number of branches in Ujwala x VKC 76, fruit length and beta carotene in Ujwala x VKC 2, average fruit weight and fruit width and girth in Ujwala x VKC 76, number of fruits per plant, yield per plant, phosphorus, calcium, magnesium in Ujwala x Anugraha, iron, vitamin C and antioxidant activity in Ujwala x VKC 11, capsaicin in Anugraha x VKC 11. Positive heterotic effect was recorded for all the characters except days to flower, days to harvest and days from flowering to harvest. Negative heterosis for days to flower showed that the hybrids were early in flowering. Positive heterotic effect over mid parent, better parent and standard parent was observed for 13 characters including plant height, fruit length, fruit width, fruit girth, average fruit weight, yield per plant, phosphorus, calcium, magnesium, capsaicin, vitamin c, antioxidant activity and beta carotene. Ujwala x VKC 76, Anugraha x VKC 2,Ujwala x VKC 2, Ujwala x VKC 11and Anugraha x VKC 76 were found to be the superior promising hybrids for yield per plant, average fruit weight, days to flower, fruit length, fruit girth, capsaicin, vitamin C and beta carotene. All the hybrids were found resistant to bacterial wilt in the field as well as when inoculated artificially with the pathogen. Promising hybrids should be evaluated for two more seasons in the field for confirming the morphological and yield traits of the hybrids. The agronomic practices for the hybrids also should be standardized.